Computational biology in Costa Rica: the role of a small country in the global context of bioinformatics - Moreno, Edgardo (2008)
The successful development of high throughput methods for DNA sequencing, transcriptomics, proteomics, and other –omics, has contributed to the emergence of novel possibilities for the examination of complex biological systems through computational analysis. These fields have witnessed unprecedented advances in high income countries. Nevertheless, the role of other nations needs to be examined in order to delineate their contribution within the global context of bioinformatics. Previous articles have focused on the expansion of Computational Biology in Brazil and Mexico [1,2], two of the largest Latin American countries, and which have shown political commitment to foster their scientific development. Costa Rica is a small Central American country with a population of 4 million, with its territory 164 and 38 times smaller than Brazil and Mexico, respectively. Thus, it is interesting to visualize the possibilities and challenges of this low-income country in the context of the global bioinformatics endeavor.